Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Pendekatan Saintifik untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar IPA Peserta Didik Kelas VIII SMP - Ni Putu Wahyu Dewi Arningsih; I Wayan Subagia; I Nyoman Tika (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2023)
This study aims to design and produce science worksheets based on a scientific approach to improve students science process skills and learning outcomes. Furthermore, the LKPD that has been prepared is tested to determine the characteristics, validity, practicality, and effectiveness of LKPD. This type of research is development research by modifying the Borg and Gall development model and the ADDIE development model with the One Group Pretest Posttest Design trial design. The instruments used were expert validation questionnaires, LKPD practicality questionnaires, science process skills observation sheets, and essay tests. The results showed that 1) Gregory's validity coefficient for the results of the material expert's validity was 0.97 with very valid criteria, the average language validity score was 97.00 with very valid criteria and the average media validity score was 96.00 with very valid criteria , 2) met the practicality requirements of the teacher with an average score of 87.00 with very practical criteria, and 3) fulfilled the effectiveness requirements with a normalized N-gain score of 0.589 with moderate criteria, an average score of science process skills in the abstract realm of 75.8 with good criteria and a concrete domain of 78 with good criteria. Based on the results of the study, it can be concluded that science worksheets based on a scientific approach can improve science process skills and student learning outcomes. Keywords: LKPD, scientific approach, KPS, learning outcomes